2018
DOI: 10.1093/rpd/ncy093
|View full text |Cite
|
Sign up to set email alerts
|

Radon and Thoron Progeny in Dutch Dwellings

Abstract: Radon and thoron progenies in Dutch dwellings cause ~400 cases of lung cancer per year. Some 30% of the risk is due to thoron progeny, which demonstrates that the influence of thoron progeny is much larger than previously anticipated. This was concluded from a national survey in 2500 Dutch dwellings, built since 1930. Radon concentrations (15.6 ± 0.3 Bq m-3 on average) are correlated to type of dwelling, year of construction, ventilation system, location (soil type) and smoking behaviour of inhabitants. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Table 3 summarizes thoron and thoron progeny concentrations (EETC) in various countries. As can be seen from the presented data, their number is more restricted than that of radon [27,39,41,42,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Radioactivity and Resulting Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes thoron and thoron progeny concentrations (EETC) in various countries. As can be seen from the presented data, their number is more restricted than that of radon [27,39,41,42,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Radioactivity and Resulting Dosementioning
confidence: 99%
“…Thoron progeny concentrations, namely equilibrium equivalent thoron concentrations (EETCs), were measured in 2900 houses, Netherlands [65]. The arithmetic mean of EETC was 0.64 Bq m −3 .…”
Section: Radioactivity and Resulting Dosementioning
confidence: 99%
“…In addition, thoron progeny concentration was measured (26)(27)(28)(29)(30). The reported radon concentration ranged from a few 10 to over 100 Bq m −3 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Cameroon study ( 29 ), thoron progeny contribution to inhalation dose was found to be 30%. Some papers showed that thoron was probably more important contribution to inhalation dose ( 27 , 30 ). A further study is required to acquire correct radon concentrations and to better evaluate the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interest in 220 Rn exposure is growing among the health sciences communities. Recently, a number of 220 Rn surveys have been carried out in local regions and nationwide, and the results have been published enabling an evaluation of exposures from 220 Rn [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Also, the need to adopt reliable 220 Rn measurement techniques has been argued in several papers [22].…”
Section: Introductionmentioning
confidence: 99%